2021
DOI: 10.1371/journal.pone.0247359
|View full text |Cite
|
Sign up to set email alerts
|

Association between in-stent neointimal characteristics and native coronary artery disease progression

Abstract: Background and aims The prognosis of stented lesions differs according to in-stent neointimal characteristics on optical coherence tomography (OCT). In particular, patients who show in-stent heterogeneous neointima are associated with a higher incidence of target lesion revascularization (TLR) compared with those who show in-stent non-heterogeneous neointima. However, the relationship between in-stent neointimal characteristics and native coronary atherosclerosis progression has not been clearly elucidated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…These findings are in line with the previous studies of Kim et al [9] where minimal lumen CSA was 4.5 ± 1.6 mm 2 and 4.0 ± 1.9 mm 2 . MLD was reported as 1.38 ± 0.33 mm and 1.36 ± 0.42 mm, which coincides with the previous study of Jung et al [11] where the mean lumen diameter was 1.1 ± 0.4 mm and 1.2 ± 0.4 mm. NIH in our study was 54.54 ± 11.23 and 59.26 ± 8.86.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are in line with the previous studies of Kim et al [9] where minimal lumen CSA was 4.5 ± 1.6 mm 2 and 4.0 ± 1.9 mm 2 . MLD was reported as 1.38 ± 0.33 mm and 1.36 ± 0.42 mm, which coincides with the previous study of Jung et al [11] where the mean lumen diameter was 1.1 ± 0.4 mm and 1.2 ± 0.4 mm. NIH in our study was 54.54 ± 11.23 and 59.26 ± 8.86.…”
Section: Discussionsupporting
confidence: 91%
“…This observation is suggestive of differential prognosis of stented lesions according to in-stent neointimal characteristics [9]. Although previous studies have explored correlations between neointimal patterns, underlying stent type, and restenosis phase, the degree of intralesional neointimal characteristics has not been elucidated [5,10,11]. Therefore, this study sought to qualitatively and quantitatively assess neointimal characteristics of lesions using OCT in patients presenting with ISR.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that subjects with neointima characterized as heterogenous have a higher risk of clinical events compared to subjects with homogenous neointima [13,27]. Additionally, heterogenous neointima might also reflect a more atherogenic milieu per se as it is associated with progression of native atherosclerosis as well [28]. Hence, heterogenous In addition, the interface includes a pullback analysis (D) that provides a detailed analysis of the OCT images and a manual correction feature (E) to correct beginning and end of the stent if necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The new plaque is at a certain distance from the trabecula of the stent, which is similar to the occurrence of coronary plaque in situ . An OCT study demonstrated that the progression of neointimal atherosclerosis after stent implantation is associated with the progression of an in situ plaque in the autologous coronary artery ( 60 ). This result is expected, as the new plaque has the same risk as the in situ plaque.…”
Section: Application Of Oct In the Post-stent Implantation Follow-upmentioning
confidence: 99%